The effects of social factors on police interactions with youth - Hankewich, Ryan (My University, 2019)
It has been recognized, socially and legally, that youth require different treatment and methodologies by the criminal justice system compared to adults. As the first point of contact within the criminal justice system, police officers’ perceptions of youth can have profound effects upon the youth they encounter. This paper critically reviews how these perceptions are formed and influenced by multiple levels of social factors. This analysis examines societal factors at the macro, meso, and micro levels, and how they influence police perceptions of youth, resulting police actions, and what level of police discretion they employ.
Keywords: criminal justice system; youth; police perceptions